The effect of short foot exercise using visual feedback on the balance and accuracy of knee joint movement in subjects with flexible flatfoot. Issue 13 (March 2020) - Kim, Ju Sang; Lee, Mi Young
Abstract: Background: Flexible flatfoot is a condition characterized by the deformations of the foot where the calcaneus is pronated by weight support. Flat feet can affect balance and the entire chain of motion, causing indirect problems in adjacent joints. We investigated the effects of short foot exercise (SFE) using visual feedback on the static balance and function of proximal joints in subjects with flexible flat feet. Method and analysis: This study involved 30 participants who were assigned to either of the 2 groups: the flexible flatfoot group (n = 15, 8 men and 7 women, aged 22.00 ± 2.07 years) and normal foot group (n = 15, 7 men and 8 women, aged 22.13 ± 1.55 years). All subjects performed the SFE with visual feedback. SFE programs were performed 20 minutes a day, 5 times a week, for a total of 5 weeks. The static balance and accuracy of knee joint motions were compared before and after training. Results: There was a significant difference in static balance pre- and post-exercise in the flatfoot group but not in the normal foot group. Moreover, in the flatfoot group, the accuracy of knee joint motions was significantly different between pre- and post-exercise in the closed chain but not in the open chain. Conclusion: This study examined the influence of SFE using visual feedback on the balance and accuracy of knee joint movements in subjects with flatfoot and demonstrated that this exercise, using visual feedback, improved the balance and accuracy of knee movement.